Peran Gereja dalam Upaya Mendukung Ekonomi Jemaat sebagai Bentuk Pelayanan Diakonia - Deny Fery Supit; Gustaf Rudolf; Suhartono Suhartono (Institut Nalanda, 2026)
As representatives of God with primary duties and as an inseparable unit of the congregation, the Church and the congregation should have a mutually beneficial relationship (symbiotic mutualism). One example of this relationship is related to the congregation's economic development. A well-off congregation can support the Church by funding various church activities. The purpose of this study is to determine the Church's role in supporting the congregation's economy as a form of diaconal ministry. The research method/technique used in this study is library research with a qualitative approach. Based on the research that has been done, it can be concluded that: First, Diakonia is a church task that is oriented towards loving service to the congregation whose implementation can be different in each Church; there are Churches that only carry out caratitative diakonia, there are also Churches that have carried out caratitative diakonia and reformative diakonia, but for transformative diakonia it has not been fully applied; Second, Diakonia is a lifestyle that is carried out/applied in the life of the early congregation and based on several studies above it can also be concluded that one of the characteristics of a healthy, growing, and developing Church is the implementation (consistently) of diakonia in the Church; Third, The development of the congregation's economy is something that is the responsibility of the Churches as a form of implementation of diakonia, and the implementation of diakonia in the context of developing the congregation's economy can be done in various ways, such as: buying sewing tools for those who can sew, buying plant seeds for those who want to garden or who want to raise livestock, through cooperatives, raising pigs, raising chickens, and micro-enterprises.